Figure 2 from: Costa AF, Siciliano S, Emin-Lima R, Martins BML, Sousa MEM, Giarrizzo T, Silva Júnior JS (2017) Stranding survey as a framework to investigate rare cetacean records of the north and north-eastern Brazilian coasts. ZooKeys 688: 111-134. https://doi.org/10.3897/zookeys.688.12636 - Costa, Alexandra Fernandes; Siciliano, Salvatore; Emin-Lima, Renata; Martins, Bruna Maria Lima; Sousa, Maura Elisabeth Moraes; Giarrizzo, Tommaso; Silva Júnior, José de Sousa e (Zenodo, 2017)
Figure 2 - Stranding events: large baleen whales. a Fin whale Balaenoptera physalus stranded at Baía do Japerica, São João de Pirabas municipality (0°45'S, 47°4.2'W), eastern coast of the Pará state. Note the good condition of the carcass and the strange swelling on the top of the head (see white arrow) (photo by GEMAM/MPEG) b A newborn Bryde's whale Balaenoptera brydei stranded on the east coast of Marajó island (0°51.6'S, 48°30'W), Pará on 15 September 2012 (photo by GEMAM/MPEG) c Humpback whale Megaptera novaeangliae stranded at Praia do Rio Novo, Tutóia municipality, Maranhão state (2°42.6'S, 42°26.4'W), note the absence of skull on the carcass (photo by A.F. Costa) d Sei whale Balaenoptera borealis stranded at Fernandes Belo, Viseu municipality (1°10.8'S, 46°5.4'W), the particular coloration of the baleen plates and slightly arched head are diagnostic characters to identify the species (photo by DEMA/PA).